FAVOURABLE OUTCOMES OF LITHIUM CARBONATE IN THE MANAGEMENT OF CONCOMITANT THYROTOXICOSIS AND ACUTE DENGUE-INDUCED HEPATITIS AND NEUTROPENIA - L, Alice Aai Lee; C, Li Yen; B, Nur Haziqah; M, Siti Nor A’thirah; M, Gunavathy; A, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Dengue is one of the most important arthropod-borne viral diseases in tropical countries. The liver is one of the most common organs affected, seen in approximately 60 to 90% of patients. It is an arduous task for clinicians to predict the clinical outcomes of dengue-induced hepatitis and neutropenia, particularly in the presence of concomitant thyrotoxicosis and the attendant risks of its therapy. Lithium has been used as an adjuvant therapy in thyrotoxicosis because of its ability to inhibit thyroid secretion. This is a case report of thyrotoxicosis complicated by dengue-induced hepatitis and neutropenia successfully treated with lithium. CASE 1: Thyroid storm triggered by dengue A 24-year-old lady with Graves’ disease presented with acute delirium on day 2 of fever. Laboratory tests included a positive dengue NS1 antigen, suppressed thyroid stimulating hormone (TSH) <0.008 mIU/L [normal value (NV), 0.55 to 4.78] and elevated free thyroxine (FT4) 118.46 pmol/L (NV 11.6 to 22.7). The diagnosis of thyroid storm was made based on delirium, fever, diarrhoea and rapid atrial fibrillation. Prompt treatment with propylthiouracil (PTU), propranolol, Lugol’s iodine, intravenous hydrocortisone and appropriate dengue supportive care were instituted. However, on day 3 of fever, the absolute neutrophil count (ANC) plummeted to 0.3 (NV 2 to 7 x 103/µL) and transaminases demonstrated an increasing trend. PTU was substituted with lithium 300 mg TDS and continued for 3 days. She recovered completely on day 6 of illness with normalized liver function tests and ANC. CASE 2: Thyrotoxicosis with dengue A 36-year-old lady with Graves’ disease on PTU 300 mg OD presented with 5 days of fever, vomiting and bleeding tendency. She was clinically in a hyperthyroid state. Laboratory tests revealed positive dengue NS1 antigen and IgM, suppressed TSH (<0.01 mIU/L), borderline FT4 (21.3 pmol/L), low ANC (0.5 x 103/µL), and elevated transaminases [ALT 213 U/L (NV 10 to 49) and AST 817 U/L (NV 0 to 34)]. She was started on intravenous N-acetylcysteine for the significant dengue-induced hepatitis. Lithium 300 mg BD was initiated instead of PTU/ carbimazole for 3 days. Liver enzymes and ANC improved, and she recovered completely on day 8 of illness. CONCLUSION Lithium is an alternative option for thyrotoxicosis especially in the setting of dengue-induced hepatitis and neutropenia.